Effect of Iron Oxide on the Protective Photochromism of African Padauk. (3rd March 2019) - Wang, Chen; Qin, Ye; Wang, Fang; Wang, Zhiping; Huang, Anmin
Abstract : African padauk is a tree whose wood is an excellent material for producing decorative items. The wood is susceptible to sunlight exposure and degrades severely, even after short exposures, which leads to discoloration. Ultraviolet irradiation is the main factor that produces discoloration. In this study, chemical changes occurring on the wood surfaces were analyzed by Fourier transform infrared spectroscopy. The discoloration of the African padauk was mainly because of the photodegradation of lignin and extractives by ultraviolet radiation. Additionally, the inhibitory effect of different concentrations of red iron oxide coating was investigated. The results revealed that the chromatism Δ E ⁎ was considerably reduced with the protection of iron oxide. However, the inhibition of the discoloration rate of the specimens covered with a film of red iron oxide increased with values reaching approximately 80%. The red iron oxide coating had a strong inhibitory effect on the discoloration of the African padauk.